Hollow carbon nanocapsule material for packaging metal and preparation method of hollow carbon nanocapsule material

By using sea urchin-like SiO2 balls to load metal and coat phenolic resin-derived carbon to prepare hollow carbon nanocapsules materials for encapsulating metals, the problem of low packaging efficiency of metal particles in the prior art is solved, efficient packaging and dispersion are achieved, and the improvement of Catalytic properties.

CN119406410APending Publication Date: 2025-02-11GUANGDONG UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411432649.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively encapsulate metal particles, which limits their application and promotion in the field of catalysis.

Method used

Sea urchin-shaped SiO2 spheres are used as the skeleton-loaded metal material, and coated with rigid hard carbon derived from phenolic resin. After etching, hollow carbon nanocapsule material for encapsulating metal is obtained.

Benefits of technology

It realizes efficient encapsulation and dispersion of metal nanoparticles, improves site exposure of metal active centers and its structural stability in hydrothermal environments, and enhances catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406410A_ABST
    Figure CN119406410A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow carbon nanocapsule material for packaging metal and a preparation method of the hollow carbon nanocapsule material, and the technical scheme comprises the following steps: S1, synthesis of sea urchin-shaped SiO2 spheres: adding cetylpyridinium bromide and urea into water, uniformly mixing, and then adding cyclohexane, isopropanol and tetraethyl orthosilicate to obtain a mixture solution; then heating the mixture solution, vigorously stirring for reaction, centrifuging, washing and freeze-drying to obtain sea urchin-shaped SiO2 spheres; s2, loading metal on the solid product obtained in the S1 by adopting an impregnation method, drying, and calcining at a high temperature in a protective atmosphere to obtain MNP / SiO2; s3, MNP / SiO2 is coated with phenolic resin, and then the obtained material is subjected to high-temperature carbonization in a protective atmosphere; s4, etching, washing and freeze-drying the material obtained in S3 in a sodium hydroxide solution to obtain a target product. According to the invention, sea urchin-shaped SiO2 spheres are used as a skeleton to load a metal material, rigid hard carbon of phenolic resin derived carbon is used for coating, and the hollow carbon nanocapsule material for packaging metal is obtained after etching. The material has porosity, large specific surface area and hollow confinement structure, and is beneficial to application and popularization in the field of catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-carbon materials, and in particular relates to a hollow carbon nano-capsule material capable of encapsulating metals and a preparation method thereof. Background Art

[0002] Carbon materials are widely used in human life and production, and the performance and application of carbon materials with special shapes and structures are also attracting more and more attention. As a nanomaterial with high specific surface area and low density, hollow carbon nanospheres not only have good permeability, high chemical and thermal stability, adsorption characteristics, non-toxicity, biocompatibility and other characteristics, but also have a regular spherical structure, which makes hollow carbon nanospheres have great potential application value in many fields such as electrochemical energy, gas storage, adsorption separation and catalysis.

[0003] In most cases, hollow nanostructures are synthesized by simple hard template methods. Typically, the desired material or its precursor is deposited on a hard template with a functionalized surface, and then the template is selectively removed by etching or thermal decomposition. There are many choices for the synthesis of precursors, such as Methods, benzoxazine methods, emulsion polymerization and dispersion polymerization methods, and hydrothermal carbonization are all good methods for synthesizing nanosphere precursors. Phenolic resins are very suitable materials for use as carbon sources because they are low in cost, easy to synthesize, and have high carbon yields (>50%). In addition, they have a strong ability to assemble with surfactants and are widely used in hard template methods.

[0004] Based on the prior art, the present invention provides a preparation method for effectively encapsulating metal particles using hollow carbon nanocapsules. First, urchin-shaped SiO2 balls are used as nanosphere precursors, and metal materials are uniformly loaded. Rigid hard carbon derived from phenolic resin is used for coating, and after etching, hollow carbon nanocapsule materials encapsulating metals are obtained. The material has universal applicability and can be used to load various metal particles, which is conducive to the application and promotion in the field of catalysis. Summary of the invention

[0005] The first object of the present invention is to provide a hollow carbon nanocapsule material that can effectively encapsulate metal particles.

[0006] The second purpose of the present invention is to provide a method for preparing the hollow carbon nanocapsule material, using sea urchin-shaped SiO2 balls as a skeleton to load the metal material, coating it with rigid hard carbon derived from phenolic resin, and obtaining the hollow carbon nanocapsule material that can encapsulate metal after etching.

[0007] To this end, the first technical solution provided by the present invention is as follows:

[0008] A method for preparing a hollow carbon nanocapsule material capable of encapsulating metal comprises the following steps in sequence:

[0009] S1: Synthesis of sea urchin-shaped SiO2 balls, adding hexadecylpyridinium bromide and urea into water and mixing them evenly, then adding cyclohexane, isopropanol and tetraethyl orthosilicate to obtain a mixture solution; then heating the mixture solution and stirring it vigorously for reaction, centrifuging it, washing it with ultrapure water, and freeze-drying it to obtain sea urchin-shaped SiO2 balls;

[0010] S2: The sea urchin-shaped SiO2 balls obtained in S1 are loaded with metals by impregnation, dried, and then calcined at high temperature in a protective atmosphere to obtain MNP / SiO2;

[0011] S3: The MNP / SiO2 obtained in S2 is uniformly dispersed in water, phenol and aldehyde are added and stirred vigorously, and the obtained material is carbonized at high temperature in a protective atmosphere to obtain MNP / SiO2@HCC;

[0012] S4: The material obtained in S3 is etched in a sodium hydroxide solution, washed with ultrapure water, and freeze-dried to obtain MNP@HCC material.

[0013] The reagents described are all commercially available reagents and do not require purification.

[0014] Furthermore, in the above-mentioned method for preparing a hollow carbon nanocapsule material capable of encapsulating metal, the heating temperature in S1 is 50-100° C., and the reaction time is 12-24 hours.

[0015] Further, in the above-mentioned method for preparing a hollow carbon nanocapsule material capable of encapsulating metal, the metal used for impregnation in S2 is one or more of Fe, Co, Ni, Cu, Zn and the like. The reagent used for impregnation is one or more of metal salts such as nitrate, carbonate, acetate and the like.

[0016] Furthermore, in the above-mentioned method for preparing a hollow carbon nanocapsule material capable of encapsulating metal, the drying temperature in S2 is 50-100° C., and the calcination temperature in an inert atmosphere is 300-500° C.

[0017] Furthermore, in the above-mentioned method for preparing a hollow carbon nanocapsule material capable of encapsulating metal, the stirring time described in S3 is 12-24 hours; and the carbonization process is calcined at 400-800° C. in an inert atmosphere.

[0018] Furthermore, in the above-mentioned method for preparing a hollow carbon nanocapsule material capable of encapsulating metal, the concentration of the sodium hydroxide solution in S4 is 0.1-1 mol / L; and the freeze-drying time is 6-12 h.

[0019] The second technical solution provided by the present invention is the above-mentioned hollow carbon nanocapsule material capable of encapsulating metal, which is prepared by the preparation method described in the first technical solution.

[0020] The second technical solution provided by the present invention is that the above-mentioned metal-encapsulated hollow carbon nanocapsule material is used to catalyze the direct synthesis of higher carbon alcohols from ethanol aqueous solution.

[0021] This application has at least the following beneficial effects:

[0022] 1. The hollow carbon nanocapsule material provided by the present invention has excellent hydrophobicity and stability, and can effectively encapsulate metal nanoparticles (MPN), making the metal nanoparticles have excellent dispersibility, thereby enhancing the exposure of the sites of metal active centers and the stability of their structures in a hydrothermal environment.

[0023] 2. The hollow shell structure of the hollow carbon nanocapsule material provided by the present invention has a large specific surface area, which can not only make the active metal highly dispersed, but also the pore structure of the carbon layer is conducive to material exchange. Such a hollow confined structure is expected to be used in catalysts to improve reaction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM images of Ni-based hollow carbon nanocapsule materials synthesized from different phenolic raw materials in Examples 1-4 of the present invention;

[0025] Figure 2 TEM image of the synthesis process of the hollow carbon nanocapsule material encapsulating Ni metal prepared in Example 1 of the present invention;

[0026] Figure 3 The XRD diagram of the synthesis process of the hollow carbon nanocapsule material encapsulating Ni metal prepared in Example 1 of the present invention;

[0027] Figure 4 TEM images of hollow carbon nanocapsule materials encapsulating Ni metal prepared at different carbonization temperatures in Examples 1 and 5 of the present invention;

[0028] Specific embodiment

[0029] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0030] Example 1

[0031] This embodiment provides a method for preparing a hollow carbon nanocapsule material capable of encapsulating metal. In this embodiment, Ni is selected as the loaded metal and the hollow carbon nanocapsule is prepared by the following method:

[0032] S1: Synthesis of sea urchin-shaped SiO2 balls: 0.5 g hexadecylpyridinium bromide and 0.3 g urea were added to 15 mL water and mixed evenly, and then 15 mL cyclohexane, 0.46 mL isopropanol and 1.25 g tetraethyl orthosilicate were added to obtain a mixture solution; the mixture solution was then heated at 75°C and stirred vigorously for 18 h, centrifuged, washed with ultrapure water 3 times, and freeze-dried for 12 h to obtain sea urchin-shaped SiO2 balls;

[0033] S2: Dissolve 0.5g nickel nitrate hexahydrate in 5mL ultrapure water, pour into 0.5g sea urchin-shaped SiO2 balls for impregnation, and place in an oven at 80℃ for drying. After drying, calcine at 450℃ for 2h in a protective atmosphere of N2 to obtain Ni / SiO2;

[0034] S3: 0.5 g Ni / SiO2 was ultrasonically dispersed in water, 0.5 g triaminophenol and 0.75 mL formaldehyde were added and stirred vigorously, the mixture was centrifuged after reacting for 24 h, washed with ultrapure water, freeze-dried for 12 h, and the freeze-dried material was carbonized at 600 °C for 3 h in a protective atmosphere of N2 to obtain Ni / SiO2@HCC;

[0035] S4: Ni / SiO2@HCC was dispersed in 40 mL of 0.5 M sodium hydroxide solution for etching, ultrasonicated for 1 h, centrifuged, washed with ultrapure water, and freeze-dried at -45 °C for 12 h to obtain Ni@HCC material, which was named Ni@HCC-3AP.

[0036] Example 2

[0037] The specific steps and process parameters of this embodiment are the same as those of embodiment 1, except that the phenol described in S3 is 0.45 g phenol, which is recorded as Ni@HCC-2.

[0038] Example 3

[0039] The specific steps and process parameters of this embodiment are the same as those of embodiment 1, except that the phenol described in S3 is 0.4 g of resorcinol, which is recorded as Ni@HCC-3.

[0040] Example 4

[0041] The specific steps and process parameters of this embodiment are the same as those of embodiment 1, except that the phenol described in S3 is 0.4 g of phloroglucinol, denoted as Ni@HCC-4.

[0042] TEM images of Ni-based hollow carbon nanocapsule materials synthesized from different phenolic raw materials in Example 1-Example 4 are as follows Figure 1The Ni-based hollow carbon nanocapsule materials synthesized in Examples 1-4 have obvious hollow structures and external carbon layer wrapped structures. The particle size of the hollow carbon nanocapsule is about 400-500nm, and the encapsulated Ni metal particles are all in a nano-scale particle dispersion state. Figure 1 (bd) It can be observed that phenol cannot construct the structure of carbon nanocapsules well, and resorcinol and phloroglucinol cannot completely maintain the hollow structure of carbon nanocapsules, and they present irregular shapes when encapsulating Ni metal particles.

[0043] The Ni@HCC-3AP material in Example 1 was characterized, and the TEM images of the materials obtained in the corresponding steps are shown in FIG. Figure 2 As shown in the figure, sea urchin-shaped SiO2 balls are used as the skeleton to load metal Ni, and the rigid hard carbon derived from phenolic resin is used to coat it. After etching, hollow carbon nanocapsule materials encapsulating Ni metal are obtained. It can be seen that Ni is evenly dispersed inside the capsule. The XRD pattern of the material obtained in the corresponding steps is shown in the figure below. Figure 3 As shown in the figure, the half-peak intensity of the characteristic diffraction peak of the corresponding metal Ni after impregnation and resin coating carbonization remains basically unchanged, indicating that the encapsulated Ni metal particles are well dispersed and not agglomerated, which is consistent with the TEM image. However, the subsequent etching step leads to a slight increase in the metal particle size, which is consistent with the conclusion of the TEM image.

[0044] Example 5

[0045] The specific steps and process parameters of this embodiment are the same as those of embodiment 1, except that the carbonization calcination temperature in S3 is 800° C., denoted as Ni@HCC-3AP-800.

[0046] The corresponding TEM images of the materials described in Example 1 and Example 5 are as follows Figure 4 (TEM images of hollow carbon nanocapsule materials encapsulating Ni metal prepared at different carbonization temperatures. (a) Ni@HCC-3AP-600, (b) Ni@HCC-3AP-800) As shown, it can be seen that hollow carbon nanocapsule materials encapsulating Ni metal were obtained at a carbonization temperature of 600°C. When the carbonization temperature was increased to 800°C, the excessively high carbonization temperature led to the collapse of the hollow carbon nanocapsule structure, and at the same time, the metal Ni was significantly agglomerated and the grain size increased.

[0047] Application Example 1

[0048] In this example, the Ni@HCC-3AP obtained in Example 1 was used to catalyze ethanol aqueous solution to directly synthesize higher carbon alcohols.

[0049] The specific steps include:

[0050] S1: 10 g of anhydrous ethanol and 10 g of ultrapure water were placed in a reactor, followed by the addition of 0.87 g of NaOH and 0.3 g of Ni@HCC-3AP catalyst, wherein the mass of catalyst: the mass of inorganic base: ethanol: water = 0.3:0.87:10:10.

[0051] S2: Initial test pressure: Under normal pressure, the catalytic reaction was carried out at 230°C for 6 hours, and the reaction products and ethanol conversion rate were detected. The test results are shown in Table 1.

[0052] Application Example 2

[0053] This application example has the same steps and parameters as those provided in Application 1, except that the catalyst provided in Example 2 is used.

[0054] Application Example 3

[0055] This application example has the same steps and parameters as those provided in Application 1, except that the catalyst provided in Example 2 is used.

[0056] Application Example 4

[0057] This application example has the same steps and parameters as those provided in Application 1, except that the catalyst provided in Example 3 is used.

[0058] Application Example 5

[0059] This application example has the same steps and parameters as those provided in Application 1, except that the catalyst provided in Example 5 is used.

[0060] Comparative Example Application Example 1

[0061] This application example has the same steps and parameters as those provided in Application 1, except that the catalyst provided by Ni / C@C is used.

[0062]

[0063] a n-OH is a straight-chain normal C4+ high-carbon alcohol, and iso-OH is a branched isomeric C6+ high-carbon alcohol.

Claims

1. A method for preparing a hollow carbon nanocapsule material for encapsulating metal, characterized in that: The steps are as follows: S1: Synthesis of sea urchin-shaped SiO2 balls: cetylpyridinium bromide and urea are added to water in a molar ratio of (1-5) and mixed evenly, and then added to a mixed solvent, heated at 50-100°C and stirred vigorously for 12-24 hours, centrifuged, washed with ultrapure water, and freeze-dried to obtain sea urchin-shaped SiO2 balls; S2: The sea urchin-shaped SiO2 balls obtained in S1 are loaded with metals by impregnation, dried, and then calcined at high temperature in a protective atmosphere to obtain MNP / SiO2; S3: The MNP / SiO2 obtained in S2 is uniformly dispersed in water, phenol and aldehyde are added and stirred vigorously, and the obtained material is carbonized at high temperature in a protective atmosphere to obtain MNP / SiO2@HCC; The molar ratio of phenol to aldehyde is 1:0.8-1.

2. S4: The material obtained in S3 is etched in a sodium hydroxide solution, washed with ultrapure water, and freeze-dried to obtain MNP@HCC material.

2. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The mixed solvent described in S1 is composed of cyclohexane, isopropanol and tetraethyl orthosilicate in a molar ratio of 2:1:

1.

3. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The metal used for impregnation described in S2 is one or more metals such as Fe, Co, Ni, Cu, and Zn.

4. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The reagent used in S2 for loading metal by the impregnation method is one or more metal salts such as nitrate, carbonate, acetate, etc.

5. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The drying temperature described in S2 is 50-100°C, and the calcination temperature in an inert atmosphere is 300-500°C.

6. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The phenol described in S3 is one of phenol, resorcinol, phloroglucinol and triaminophenol; the aldehyde described in S3 is formaldehyde.

7. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The stirring time described in S3 is 12-24 hours; the carbonization process is calcined at 400-800° C. in an inert atmosphere.

8. The method for preparing a metal encapsulated hollow carbon nanocapsule material according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in S4 is 0.1-1 mol / L; the freeze-drying time is 6-12h.

9. A hollow carbon nanocapsule material for encapsulating metal, characterized in that: Prepared by the preparation method described in claims 1-8.

10. The metal encapsulated hollow carbon nanocapsule material according to claim 1 is used for catalyzing the direct synthesis of higher alcohols from ethanol aqueous solution.

Citation Information

Patent Citations

  • Hollow carbon ball encapsulated Ru nano particle electrolysed water catalyst and preparation method thereof

    CN108531932A

  • Carbon nanoflower coated carbon sphere material with core-shell structure as well as preparation method and application of carbon nanoflower coated carbon sphere material

    CN116812914A